Faktor yang Mempengaruhi Penegasan Privasi pada Transformasi Ruang Huntap Dongkelsari - Desy Candramaya; Ardhya Nareswari (Jurnal Teknologi dan Desain, 2021)
Huntap is designed as a house that can be improved from time to time until it becomes permanent settlement in accordance with the wishes of its inhabitants. People who live in huntap initially lived in large houses with large yards with a spread pattern of settlements and at the time of relocation of these communities had to be moved and lived in settlements with limited land area with cluster-shaped settlement patterns. This study aims to determine the factors and elements that influence the privacy affirmation in the space transformation of the Huntap Dongkelsari. Factors affecting privacy affirmation can be divided into territorial, security, and personal factors. Elements of privacy affirmation can be elements that explicitly mark boundaries and privacy (such as boxes, fences, and partition walls in the form of brick or plywood) and elements that implicitly mark boundaries and privacy (such as wooden cabinets, chicken coops, fish ponds, and drilled wells). The use of these elements is influenced by the need for privacy, the need for security, occupant’s experience and habits conducted in the previous house.